Peningkatan Pengetahuan Masyarakat dalam Pengelolaan Hutan Berbasis Ekonomi Berkelanjutan di Desa Pudeng, Provinsi Aceh - Bakruddin Bakruddin; Cut Maila Hanum; Eka Sri Wulandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Sustainable forest management plays a crucial role in maintaining ecosystem balance and improving community welfare, particularly within social forestry areas. This community service program was conducted in Pudeng Village, Aceh Besar District, an area under the Community Forest (HKm) permit managed by the Tuah Sejati (KTH). The program aimed to enhance community knowledge regarding social forestry regulations, sustainable forest management, and community-based ecotourism. Evaluation was carried out using a pre-test and post-test instrument consisting of eight multiple-choice questions, completed by 18 participants. The results indicate an increase in the average understanding level from 59.85% in the pre-test to 68.88% in the post-test, with the highest improvement observed in ecotourism-related topics (+23.53%) and ecotourism principles (+17.65%). Conversely, a significant decline was noted in the understanding of social forestry regulations (–19.93%). These findings highlight the need to simplify the delivery of regulatory materials to improve comprehension. Overall, the program was effective in enhancing participants’ practical knowledge related to forest management and ecotourism development.